2010
DOI: 10.1140/epjb/e2010-00141-3
|View full text |Cite
|
Sign up to set email alerts
|

Spin density wave in oxypnictide superconductors in a three-band model

Abstract: The spin density wave and its temperature dependence in oxypnictide are studied in a threeband model. The spin susceptibilities with various interactions are calculated in the random phase approximation(PPA). It is found that the spin susceptibility peaks around the M point show a spin density wave(SDW) with momentum (0, π) and a clear stripe-like spin configuration. The intraband Coulomb repulsion enhances remarkably the SDW but the Hund's coupling weakens it. It is shown that a new resonance appears at highe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 17 publications
(19 reference statements)
3
11
0
Order By: Relevance
“…86 We note that there are several alternative three-orbital models which display an xy-dominated hole pocket at the M point. 44,53 A similar analysis to that performed here has been carried out for such a three-orbital model, 62 and the susceptibility was found to be peaked at an incommensurate wavevector close to (π, 0). More recently, Zhou and Wang studied a three-orbital model of LaFeAsO using Gutzwiller mean-field theory restricted to two-site magnetic unit cells and found significant deviations from the usual Hartree-Fock approach.…”
Section: Resultssupporting
confidence: 70%
“…86 We note that there are several alternative three-orbital models which display an xy-dominated hole pocket at the M point. 44,53 A similar analysis to that performed here has been carried out for such a three-orbital model, 62 and the susceptibility was found to be peaked at an incommensurate wavevector close to (π, 0). More recently, Zhou and Wang studied a three-orbital model of LaFeAsO using Gutzwiller mean-field theory restricted to two-site magnetic unit cells and found significant deviations from the usual Hartree-Fock approach.…”
Section: Resultssupporting
confidence: 70%
“…The various theoretical attempts have been made based on the two orbital [29][30][31][32]33], three orbital [19,20,34,35] and also five 3d orbital per site models [36]. Recently, we have theoretically analyzed the spectral function of electronic states within two orbital per site tight binding model for iron pnictide superconductors and pointed out that the Hund's coupling term accumulate the spectral weight (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…It is pointed out that band renormalization is anisotropic due to Coulomb interaction and dominated by orbital physics close to (0, p) point. Long et al [35] found that in iron based system at the (0, p) point, spin density wave (SDW) peak enhanced due to the intra-orbital Coulomb interaction, while it reduced with Hund's coupling energy. Therefore, the onsite intra and inter-orbital Coulomb interactions and Hund's coupling energy play an essential role in understanding the physics of multi-orbital in superconducting state of iron pnictide/chalcogenide systems.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations